PSYCHOLOGICAL TRAINING OF WRESTLERS TAKING INTO ACCOUNT THE TYPES OF TEMPERAMENT AT THE PRE-COMPETITIVE STAGE - Kuznetsov, A.S.; Zekrin, F.Kh.; Chernova, G.M.; Mustaev, R.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to determine the influence of the psychological training of Greco-Roman wrestlers on the basis of taking into account the types of temperament at the pre-competitive stage of the training process. Methods and structure of the study. In a scientific experiment conducted with the help of a questionnaire, 30 sportsmen took part, engaged in Greco-Roman style wrestling, stages of improvement of sports skills and higher sports skills. To determine the types of temperament of spores, we used G. Eysenck's test. Results and conclusions. In the Greco-Roman wrestlers of the experimental group, under the influence of the developed methodology on the basis of taking into account individual peculiar properties of the psyche at the pre-competitive stage, the state of mental readiness of the wrestlers changed statistically significantly with a confidence probability q= 0.95. The data obtained testify to the need for purposeful work to improve the sports training of Greco-Roman style wrestlers, taking into account the individual properties of the psyche.